How to raise an amazing child the Montessori way : a parents' guide to building creativity, confidence, and independence - Seldin, Tim, 1946- (DK Publishing, 2025)
"Packed with Montessori-based preschool activities and educational games that build confidence and independence through active learning, this authoritative illustrated guide helps raise self-reliant and creative children. Celebrate physical and intellectual milestones from birth to age six with activity checklists, and encourage development through proven child-centered teaching methods. This edition has been updated to include the latest child development research, advice about screen time in the digital age and a contemporary approach to cultural education"--